A catalytic highly enantioselective allene approach to oxazolines. Issue 7 (23rd January 2018) - Luo, Hongwen; Yang, Zheng; Lin, Weilong; Zheng, Yangguangyan; Ma, Shengming
Abstract : A completely different approach for the asymmetric construction of oxazoline derivatives with an excellent enantioselectivity via the palladium-catalyzed coupling-cyclization of N -(buta-2, 3-dienyl)amides with aryl iodides has been reported. Abstract : Oxazolines are a very important class of heterocyclic compounds. However, catalytic enantioselective syntheses are very limited. Here, a highly enantioselective palladium-catalyzed coupling-cyclization of readily available N -(buta-2, 3-dienyl) amides with aryl or 1-alkenyl iodides has been developed for the asymmetric construction of oxazoline derivatives. Many synthetically useful functional groups are tolerated in this reaction. The absolute configuration of the chiral center in the products has been established by X-ray diffraction study. A model for prediction of the absolute configuration of the chiral center in the products from this cyclic enantioselective nucleophilic allylation has been proposed. The synthetic potentials based on the unique structure of the products formed have also been demonstrated.